2004
DOI: 10.1002/zoo.20007
|View full text |Cite
|
Sign up to set email alerts
|

Proximate, vitamins A and E, and mineral composition of free‐ranging cotton mice (Peromyscus gossypinus) from St. Catherines Island, Georgia

Abstract: Although rodents are an integral part of numerous carnivore diets, there is little published information regarding nutrient composition in free-ranging mice for comparison with laboratory-reared prey. Cotton mice (Peromyscus gossypinus, n ¼ 6) were captured on St. Catherines Island, Georgia, and analyzed for water, ash, protein, and fat content (proximate constituents), as well as minerals and the fatsoluble vitamins A and E. The overall body composition (mean7SD: 65.8%71.9% water, 10.9%72.2% ash, 56.4%74.1% p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…In any case, both species appear to contain adequate vitamin E as food for ferrets compared to estimated dietary requirements of mink or domestic carnivores (~30 IU/kg DM for maintenance and 80 IU/kg DM for reproduction; National Research Council 1982, 2006). While prairie dog values were similar to those measured in free‐ranging cotton mice (Thomas et al 2004) and within ranges reported for medium‐sized prey species such as rats or rabbits, these vitamin E levels measured are markedly higher than vitamin E concentrations reported in domestically reared small prey rodents (mice, hamsters; Dierenfeld et al 2002). Prey sourcing therefore requires careful consideration for captive carnivore diet formulation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In any case, both species appear to contain adequate vitamin E as food for ferrets compared to estimated dietary requirements of mink or domestic carnivores (~30 IU/kg DM for maintenance and 80 IU/kg DM for reproduction; National Research Council 1982, 2006). While prairie dog values were similar to those measured in free‐ranging cotton mice (Thomas et al 2004) and within ranges reported for medium‐sized prey species such as rats or rabbits, these vitamin E levels measured are markedly higher than vitamin E concentrations reported in domestically reared small prey rodents (mice, hamsters; Dierenfeld et al 2002). Prey sourcing therefore requires careful consideration for captive carnivore diet formulation.…”
Section: Discussionsupporting
confidence: 79%
“…Without knowledge of this component's contribution, interpretation of vitamin A intake by ferrets outside of the breeding season based on prairie dog carcass composition alone would be misleading. Very few values for vitamin A content in whole rodent prey are found in the literature (Douglas et al 1994, Clum et al 1996, Dierenfeld et al 2002; captive-reared rodents consistently demonstrated high and widely varying levels of this nutrient, especially compared to values measured in free-range cotton mice (Peromyscus gossypinus; Thomas et al 2004). The detection of vitamin A in some stomach samples was unexpected as plants contain no preformed vitamin A but rather carotenoid precursors utilized by herbivores to convert into active forms in the intestinal tract.…”
Section: Discussionmentioning
confidence: 99%